1997
DOI: 10.1007/bf02739704
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of p53 in human thyroid neoplasms: Correlation with biological behavior

Abstract: Molecular analyses of thyroid tumors have documented mutations in the tumor suppressor p53 gene almost exclusively in anaplastic carcinomas. In contrast, immunohistochemistry has localized p53 in differentiated papillary and follicular thyroid cancers. To establish the significance of p53 immunolocalization in these lesions, 78 thyroid tumors of follicular derivation were examined. All tumors were classified by strict criteria and the extent of tumor was determined morphologically. Immunohistochemical staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 19 publications
4
34
0
Order By: Relevance
“…Intragenic p53 mutations have been long recognized to be infrequent in primary human thyroid carcinomas (Ito et al 1992); they are associated with loss of differentiation and with the most aggressive tumors (Donghi et al 1993, Fagin et al 1993. Nevertheless, altered p53 immunoreactivity that may not reflect mutation has been described in several studies (Hosal et al 1997). The current study using a relatively large-sample size again demonstrated variable p53 immunoreactivity in thyroid carcinomas.…”
Section: Discussionsupporting
confidence: 54%
“…Intragenic p53 mutations have been long recognized to be infrequent in primary human thyroid carcinomas (Ito et al 1992); they are associated with loss of differentiation and with the most aggressive tumors (Donghi et al 1993, Fagin et al 1993. Nevertheless, altered p53 immunoreactivity that may not reflect mutation has been described in several studies (Hosal et al 1997). The current study using a relatively large-sample size again demonstrated variable p53 immunoreactivity in thyroid carcinomas.…”
Section: Discussionsupporting
confidence: 54%
“…However, p53 expression was observed in well-differentiated (10-18%) and poorly differentiated (40-80%) thyroid carcinomas, in one study. 31 Mutation and overexpression of p53 were observed more often in PTC when lymph node metastasis was present, 8 or when dedifferentiation to anaplastic carcinoma had occurred. 32,33 According to Hosal et al 8 and Godballe et al, 9 p53 expression is a significant independent prognostic indicator of PTC.…”
Section: Discussionmentioning
confidence: 99%
“…7 Immunohistochemical examination is typically performed not to diagnose follicular tumours of the thyroid gland, but rather to distinguish between types of follicular tumour; 6,7 such analysis is more helpful in predicting the patient's prognosis, rather than in confirming the diagnosis. Epidermal growth factor (EGFR) expression 8 and p53 expression 9 have been found to be significant independent prognostic factors for thyroid cancer. 10,11 The extent of surgery is generally chosen by analysis of risk factors (such as age, sex, extrathyroidal extension and radiation history), and total thyroidectomy is usually performed in those patients classified as high risk.…”
Section: Introductionmentioning
confidence: 99%
“…Another signaling pathway implicated in FTC is the phosphatidylinositol-3-kinase (PI3K)=AKT pathway, which is highlighted below and in Table 2. Other genetic alterations such as loss of p53 function and b-catenin activating mutation have been detected late in tumor development (63)(64)(65)(66).…”
Section: Ftcmentioning
confidence: 99%